Antimicrobial Prescription Habits of Dentists Performing Dental Implant Treatments in Santo Domingo, Dominican Republic - Juan Manuel Aragoneses; Javier Aragoneses; Vanessa Arlette Brugal; Juan Algar; Ana Suarez (MDPI AG, 2020)
The use of antibiotics in implant treatments is controversial. The purpose of this research was to study the behaviors of Santo Domingo dentists who prescribe antimicrobials to patients for the placement of dental implants. A total of 99 dentists participated in the study. A share of 1.2% of dentists prescribed antimicrobials solely in the preoperative period, 8.6% after surgery, 44.4% before and after, 19.8% only in specific situations, and 25.9% did not prescribe at all. Amoxicillin was the predominant antimicrobial of choice. A cross-sectional, observational, survey-based study was conducted. The items studied were demographics, self-assessment of knowledge about antibiotics and when they are used, as well as their recommended dosage and duration, in healthy and non-allergic patients. Notable variability was found in the prescription behaviors of antimicrobials. Bridging gaps in knowledge on the subject could help to standardize prescription guidelines.